Human placental trophoblast cells contribute to maternal–fetal tolerance through expressing IL-35 and mediating iTR35 conversion - Liu, Jia; Hao, Shengnan; Chen, Xi; Zhao, Hui; Du, Lutao; Ren, Hanxiao; Wang, Chuanxin; Mao, Haiting (Nature communications, 2019)
During pregnancy, trophoblast cells sustain the maternal–fetal tolerance via expressing and secreting various chemokines and cytokines. Our previous study revealed the expression of interleukin-35 (IL-35) in human first-trimester trophoblasts. Here we show that IL-35 is expressed in both human first-trimester primary trophoblast cells and a trophoblast cell line. Trophoblast cells inhibit the proliferation of human naive conventional T cells (T conv cells) and convert suppressed T conv cells into iT R 35 in an IL-35-dependent manner. Mechanistically, trophoblast cell derived IL-35 mediates its function through phosphorylation of STAT1 and STAT3. In vivo studies confirm that mice with immunologically spontaneous abortion have lower levels of IL-35 and iT R 35 cells at the maternal–fetal interface, and neutralizing anti-IL-35 mAb enhances abortion rates. Meanwhile, exogenous IL-35 induces iT R 35 and prevents immunological abortion. Our findings thus suggest that trophoblast cells have a critical function in preserving maternal–fetal tolerance via secreting IL-35 during pregnancy. Trophoblasts play a critical role in maintaining immunological tolerance at maternal–fetal interface. Here the authors show that IL-35 is made by trophoblasts, converts T cells to immune tolerant iTR35 cells, and is critical to prevent spontaneous abortion.